Analisis Kelengkapan Rekam Medis Dengan Kelayakan Klaim BPJS Pasien Rawat Inap - Jayanti, Asykar; Waskito, Dito Yogo; Sugiarsi, Sri (Politeknik Negeri Jember, 2025)
Dr. Soeradji Tirtonegoro General Hospital, as a Public Service Agency in collaboration with BPJS Kesehatan, has encountered challenges in achieving patient service claim targets. In June 2024, 71.23% of submitted claims were deemed eligible, while 28.77% were pending out of 1,950 total claims, resulting in the hospital’s Director Performance Index target of 93.75% for resolving pending BPJS Kesehatan claims not being met. This study aims to analyze the relationship between medical record completeness and the eligibility of inpatient BPJS Kesehatan claims. An observational analytic approach with a cross-sectional design was applied to a sample of 361 inpatient BPJS Kesehatan claim files submitted between September and November 2024. Data analysis was conducted using the Fisher Exact Test with SPSS version 23. The results revealed a significant relationship between medical record completeness and claim eligibility (p = 0.000). It is therefore recommended that healthcare professionals and coders pay greater attention to aspects influencing the accuracy of claim documents by providing specific diagnoses and procedures, strengthening coder competencies to ensure precise diagnostic coding, and implementing concurrent analysis prior to patient discharge with the involvement of case managers, in order to minimize incomplete medical records and reduce pending claims.